Peripheral giant cell granuloma: A review of 123 cases - Niloofar Shadman; Shahram Farzin Ebrahimi; Shahin Jafari; Mohammad Eslami (Wolters Kluwer Medknow Publications, 2009)
Background: Peripheral giant cell granuloma is one of the reactive hyperplastic lesions of the oral cavity, which originates from the periosteum or periodontal membrane following local irritation or chronic trauma. The purpose of this study was to present the clinical characteristics of peripheral gi-ant cell granuloma in a group of Iranian population. Methods: A series of 123 consecutive confirmed cases of peripheral giant cell granuloma after biopsy were evaluated. Age, sex, anatomic location, consistency, etiologic factor, pain and bleeding history, color, surface texture, and pedicle situation were recorded and were analyzed by chi-square test and values were considered to be significant if P < 0.05. Results: Age ranged from 6 to 75 years (mean 33 years). Women affected more than men (M/F 1:1.1). Peripheral giant cell granuloma was seen in the mandible more than in the maxilla and in the anterior region more than in the posterior region. In most cases, lesions were pink, pedunculated and had non-ulcerated surface. In less than half of the cases, there was no history of bleeding and also pain was rarely reported. Calculus was the most common etiologic factor. Conclusion: The results confirmed that the clinical features of peripheral giant cell granuloma in a group of Iranian population are almost similar to those reported by other investigators.